Modification whey protein properties with use cross linking agent - Fursik, Oksana; Strashynskyi, Igor (My University, 2021)
The most important physiological and biological properties, that reflect value of food, are compliance of the chemical structure its components, as well as the balance of nutrients, namely macro- and micronutrients, vitamins, amino acids, etc. Dietary proteins, in addition to being used as an energy source and provide the body with amino acids for protein synthesis, are important biological objects that help maintain overall human health, participate in the growth and development of the body, the functioning of cellular metabolism
Keywords: кафедра технології м’яса і м’ясних продуктів; metabolism; protein properties; dietary proteins